Replacing screen time, with physical activity and sleep time: influence on cardiovascular indicators and inflammatory markers in Brazilian children - Luiza N. Reis; Cezane P. Reuter; Anthony Okely; Caroline Brand; Camila F. Fochesatto; Clarice M.L. Martins; Jorge Mota; Adroaldo C.A. Gaya; Anelise R. Gaya (Elsevier, 2024)
Objective: To examine if the substitution of different screen time intervals with light physical activity (LPA), moderate to vigorous physical activity (MVPA) and sleep is associated with cardiovascular indicators and inflammatory markers in children. Methods: This is a cross-sectional study developed with 186 children aged between six and 11 years old from public schools in southern Brazil. CRF was measured with the 6-minute running and walking test, following the Brazil Sports Project procedures. The percentage of fat was evaluated through DXA. LPA and MVPA were measured using accelerometers. Sleep and screen time were assessed by questionnaires answered by parents. Leptin and C-reactive protein were measured by fasting blood collection. Systolic and diastolic blood pressure were determined through a digital sphygmomanometer. Isotemporal substitution models were used for statistical analysis. Results: Replacing 1 h of screen time with MVPA was associated with lower BMI, systolic and diastolic blood pressure, fat percentage, leptin, and C-reactive protein. When screen time was substituted for sleep time, lower waist circumference was observed. Regarding the substitution of 1 h of screen time with LPA, significant values were found only for leptin. Conclusion: The replacement of screen time with physical activities of different intensities and sleep time was associated with benefits in cardiovascular indicators and inflammatory markers in childhood.